THE POLITICAL ECONOMY OF TRANSFER PRICING: ITS CONTRIBUTION TO TAX AVOIDANCE AND WEALTH RETENTIVENESS - Poniman; Lilik Purwanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This article examines transfer pricing not as a neutral technical mechanism for allocating costs and revenues, but as a strategic instrument used by multinational enterprises to engage in tax avoidance and consolidate wealth. Drawing on a critical accounting framework, it builds on Sikka and Willmott (2010), who show that intra-group pricing constitutes a politico-economic practice that enables the systematic shifting of profits to low-tax jurisdictions, thereby eroding the tax base of countries where real economic activity takes place. The analysis highlights how corporations mobilize technical legitimations such as claims of arm’s length pricing to construct new “truths” about fair value that are difficult for tax authorities to contest, particularly in developing countries with limited regulatory and audit capacity. Through a Foucauldian lens, transfer pricing is interpreted as a technology of power that reinforces the dominance of global capital over nation-states by controlling profit flows, structuring asymmetric regulatory negotiations, and deepening fiscal inequalities. The article thus argues that transfer pricing is a practice deeply embedded in vested interests and power relations, with significant implications for tax justice, state fiscal capacity, and the distribution of wealth in the global economy.